The process of politicization : how much politics does a society need? - Wacławczyk, Wiesław; Jarosz, Adam (CGS studies ;, 2017)
The problem signalled in the title of this volume is of utmost importance today. While envisioning a completely depoliticised society requires a big leap of imagination, there can still be doubts as to the degree to which modern societies may or should be politicised in different dimensions. This book gives a range of answers to this question using selected examples from modern history and the present time, and it outlines the process of politicising the society, together with the tools and means used for that. It does not attempt an exhaustive coverage of the topic of politicisation but serve.